Análise de perigos e pontos críticos de controle (APPCC) em abatedouros de frangos no Brasil: uma revisão sistemática - (:unkn) unknown (Universidade Federal do Pampa, 2015)
Hazard Analysis and Critical Control Points (HACCP) is a quality program implemented in slaughtering chickens as food safety assurance measure. The objective of this study was to analyze the development of the HACCP plan and its application in poultry slaughtering process in Brazil. Did a literature search using the keywords "HACCP" short and in words, "chicken" and its equivalents in English and for the selection of articles, it was stipulated criteria related to the implementation of the HACCP Plan. It selected 24 studies, six of them Brazilian articles and demonstrating the difficulty in finding publications on HACCP in the food industry. As to the law, the most cited was Ordinance No. 210/1998. There was monitoring a large number of biological hazards, such as Salmonella, Campylobacter and fecal coliform. Much of this had the effect assessed randomly in slaughtering chickens, with a few definitions of Critical Control Points (CCP). The most critical steps for slaughter were gutting, cleaning, pre-cooling and plucking. These steps require greater monitoring and often sources of cross-contamination. Therefore, it is concluded that due to the difficulties in defining CPC HACCP plan, monitoring the production of chicken chain by the competent bodies is necessary.
Keywords: APPCC; Frango; Gestão da qualidade total; Inocuidade dos alimentos; HACCP; Poultry; Total quality management; Food safety; CNPQ::CIENCIAS AGRARIAS